Using pediatric liver grafts (≤6 yr) for adult recipients: A considerable option?. (8th September 2015) - Schukfeh, Nagoud; Paul, Andreas; Gallinat, Anja; Hoyer, Dieter P.; Treckmann, Jürgen W.; Minor, Thomas; Sotiropoulos, Georgios C.; Metzelder, Martin L.; Schulze, Maren
Abstract: In LT, the common policy is to allocate pediatric liver grafts to pediatric recipients. Pediatric organs are also offered to adults if there is no pediatric recipient. However, they are rarely accepted for adult recipients. So far, there is no information available reporting outcome of LT in adult recipients using pediatric livers from donors ≤6 yr. In this study, we included nine adult recipients (seven females and two males) who received grafts from children ≤6 yr from January 2008 to December 2013. We evaluated the graft quality, the GBWR and analyzed the recipients' perioperative course. Laboratory samples and graft perfusion were analyzed. Nine adults with a median age of 49 yr (range: 25–65) and a median weight of 60 kg (range: 48–64) underwent LT with a pediatric donor graft. Median donor age was five yr (range: 3–6). Median GBWR was 1.02 (range: 0.86–1.45). After a median follow‐up of 3.9 yr (range: 11 months–6.6 yr), patient survival was 100%; graft survival was 89%. One patient needed re‐transplantation on the second postoperative day due to PNF. Eight recipients were discharged from the ICU after 2–9 days with a regular graft function. Doppler scans revealed regular flow patterns at any time. Only if denied for pediatric recipients, the use of pediatric livers from donors ≤6 yr for adult recipients is a considerable option.